Functionally-Relevant Morphological Profiling: A Tool to Assess Cellular Heterogeneity. Issue 1 (January 2018) - Marklein, Ross A.; Lam, Johnny; Guvendiren, Murat; Sung, Kyung E.; Bauer, Steven R.
Abstract : Heterogeneity in cell function has presented a significant hurdle to the successful clinical translation of many cellular therapies. Current techniques for assessing cell quality and the effects of microenvironmental cues and manufacturing processes on cell behavior often inadequately address heterogeneity due to issues such as population versus single-cell measurements and the therapeutic relevance and throughput/robustness of the assay. Due to the well-established relationship between morphology and cellular function, morphological profiling has become increasingly utilized to better understand functional heterogeneity and its impact on therapeutic development. In this review, we introduce an emerging field we term functionally-relevant morphological profiling with great potential to improve our understanding of cellular heterogeneity through discovering novel quality attributes, optimizing manufacturing, and screening drugs/biomaterials. Trends: Single cell and multicellular morphological features represent a summation of signaling events indicative of phenotype and function. Advances in automated microscopy and image analysis have driven morphology-based research due to increased accessibility and throughput of imaging technologies. Functionally-relevant morphological profiling may facilitate identification of novel critical quality attributes of cell therapies, which can be used to further refine and improve cell manufacturing processes. Morphological profiling permits high-throughput screening/evaluation of biomaterial and functional/toxicological agents and can aid in the development of advanced 3-D organotypic models.